BIMBINGAN KONSELING ISLAMI SEBAGAI UPAYA PEMBENTUKAN KARAKTER PESERTA DIDIK YANG BERAHKLAKUL KARIMAH - M. Alhidayah Tullah; M. Sodikin; M. Ichsan Dwi Saputra; Randy (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2026)
Islamic Guidance and Counseling is one of the educational programs directed toward efforts to reform education based on Islamic values. Through guidance and counseling programs, the development of students’ psychological well-being is emphasized, particularly in enhancing their mental, spiritual, and moral capacities in accordance with akhlaq al-karimah. The results of the study indicate that Islamic Guidance and Counseling does not merely focus on resolving students’ problems, but also emphasizes the process of internalizing values of faith, piety, and noble character. The approaches applied in Islamic Guidance and Counseling include role modeling, habituation, advice, religious dialogue, and self-reflection (muhasabah), which are directed toward developing students’ moral awareness. Through a guidance process integrated with Islamic values, students are assisted in recognizing their personal potential, controlling negative behavior, and developing attitudes and behaviors that align with Islamic teachings. Thus, Islamic Guidance and Counseling plays a strategic role in shaping students’ character with akhlaq al-karimah and enabling them to apply these values in their daily lives. This article aims to examine the role of Islamic Guidance and Counseling as an effort to develop students’ character with akhlaq al-karimah within the educational environment. This study employs a qualitative approach using a literature review method, drawing upon sources from the Qur’an and Hadith, as well as relevant scientific literature related to Islamic Guidance and Counseling and character education.